Konseling Kelompok Berbasis Cybercounseling Pendekatan Rational Emotive Behaviour Theraphy (REBT) untuk Meningkatkan Kontrol Diri Siswa - Ifan Setiawan; Heru Mugiarso (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
This study aims to determine the effect of group counseling services based on rational emotive behavior therapy with cybercounseling approach on students' self-control. This research design is pre-experimental research with one group pre-test and post-test research design. The Participants of this study was 8 students recruited using the criteria of sampling technique. The data was collected using a psychological scale that was developed based on indicators from other studies which analyzed using the Wilcoxon analysis technique. The results showed that the level of self-control of students who were given group counseling services group counseling services based on rational emotive behavior therapy with cybercounseling approach increased by 23.36%. This study also proved that group counseling services based on group counseling services based on rational emotive behavior therapy with cybercounseling approach affect students' self-control.